New species and new records of Amasa Lea, 1894 ambrosia beetles from Thailand (Coleoptera: Curculionidae: Scolytinae: Xyleborini) - Sittichaya, Wisut; Smith, Sarah M. (Zootaxa, 2022)
Three new species, Amasa beaveri sp. nov., Amasa cognatoi sp. nov., and Amasa macarthorum sp. nov., are described. Three species, Amasa circumcisula (Schedl, 1954), Amasa dasyura (Browne, 1950) and Amasa latetruncata (Schedl, 1942), are recorded in Thailand for the first time. A synoptic list of the Thai fauna with distributions is also provided.